To compare between objective evaluation of nasality using nasometer and perceptual evaluation of nasality among children and adults with cleft palate: a preliminary study - Kamaruddin, Afiqah Iylia (Universiti Sains Malaysia, 2012)
One of the most common birth defect and congenital defect of the craniofacial is cleft lip and palate. The speech characteristic commonly associated with cleft palate population is hypemasality. Traditionally, Speech Language Pathologists (SLPs) used perceptual evaluation to evaluate the nasality of one’s speech. As technology is advancing, a number of instruments are now available to be used as an objective evaluation to evaluate nasality for example, Nasometer. A cross sectional study on nasometry analysis was conducted to investigate the effectiveness of Nasometer as an objective evaluation for nasality among cleft palate population. The participants were 8 repaired cleft palate patients from Surgery Out-Patient Department (SOPD) in HUSM. Kay Nasometer model 6400 was used as an objective evaluation to obtain the mean nasalance scores for each participant. Three reading stimuli in Bahasa Melayu constructed by Abdul Wahab et al. (2004) were used to measure the mean nasalance scores. Three SLPs listened to the audio recordings and rate the severity of the hypemasality using seven-point equal-appearing interval scale. The results showed mean nasalance scores of 75.68% for nasal passage, 67.38% for oral passage, and 67.75% for oronasal passage. There was a good intra-rater reliability and moderate to good inter-rater reliability. There was no correlation between objective evaluation using Nasometer and perceptual evaluation using seven-point equal-appearing interval scale. The results found in this study showed that Nasometer is effective to be used as an objective evaluation of nasality among children and adults with repaired cleft palate.